Challenges in Building a Secure Sustainable Society Amid Global Risks and Threats: Theoretical and Practical Aspects - Vilks, Andrejs; Kipane, Aldona; Kuzņecova, Kristine (European Journal of Sustainable Development, 2024)
The development of society must be based on its sustainability. The current geopolitical situation is linked to extensive security challenges, new extremist manifestations, and threats at international and national levels. In today